Cartilage Oligomeric Matrix Protein Induced Arthritis—A New Model for Rheumatoid Arthritis in the C57BL/6 Mouse - Zhao, Yunjuan; Urbonaviciute, Vilma; Xu, Bingze; Cai, Weiwei; Sener, Zeynep; Ge, Changrong; Holmdahl, Rikard (Frontiers in Immunology, 2021)
The most commonly used strains in experimental research, including genetically modified strains, are C57BL/6 mice. However, so far, no reliable model for rheumatoid arthritis is available, mainly due to the restriction by the MHC class II haplotype H-2b. Collagen-induced arthritis (CIA) is the most widely used animal model of rheumatoid arthritis, but C57BL/6 strain is resistant to CIA because there is no collagen II peptide associated with H-2b. To establish a rheumatoid arthritis model in C57BL/6 mice, we immunized C57BL/6NJ (B6N) mice with human cartilage oligomeric matrix protein (COMP), which induced severe arthritis with high incidence, accompanied by a strong auto-antibody response. Native COMP was required, as denatured COMP lost its ability to induce arthritis in B6N mice. An immunodominant COMP peptide was identified as the key T cell epitope, with a perfect fit into the Ab class II peptide binding pocket. A critical amino acid in this peptide was found to be phenylalanine at position 95. Recombinant COMP mutated at position 95 (COMP_F95S) lost its ability to induce arthritis or a strong immune response in the B6N mice. In conclusion, A new model for RA has been established using C57BL/6 mice through immunization with COMP, which is dependent on a COMP specific peptide binding Ab, thus in similarity with CIA in Aq expressing strains.